(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
One of the key problems in the departments of anesthesiology and intensive care is the energy deficit in patients. To resolve this, critically ill patients are prescribed parenteral nutrition, which contains fat emulsions. It is known that essential fatty acids in fat emulsions can exhibit both pro-inflammatory (linoleic acid) and anti-inflammatory (linolenic acid) effects. In order to reduce the impact on the immune system, it is recommended to use alternative fat emulsions, as this can provide better clinical results. The first generation of fat emulsions consisted of soybean oil, but it has been proven that it can increase the risk of purulent-septic complications. The second generation of fat emulsions contains medium-chain triglycerides, the metabolism of which can lead to acidosis, so their use is limited, especially in patients with diabetes mellitus. Third-generation fat emulsions contain olive oil, which reduces the risk of thrombosis, is considered immunoneutral and less sensitive to lipid peroxidation. The fourth generation of fat emulsions includes fish oil, which has anti-inflammatory properties and can reduce the length of stay of patients in critical condition. It is most promising to use balanced fats, among which Omega-3 Fatty Acids, is commonly used in Nigeria. It has been proven that for patients in need of parenteral nutrition, fat emulsions are an integral part of it, and patients in critical condition are recommended to use fat emulsions containing fish oil. However, it is recommended to assess the initial level of triglycerides before prescribing. In view of the above, it can be concluded that lipids provide the needed fatty acids that affect important processes of the body, including metabolism, immune response, blood clotting. Alternative fat emulsions may be a better source of energy, also exhibiting antioxidant effects and less suppression of immunity.